Pendampingan Pembuatan Portofolio Event Organizer di Seirah Wisata Ali Takrim - Surojudin, Nurhadi; Putra, Fibi Eko; Effendi, M. Makmun; Suryadi (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
This community service activity aims to assist Seirah Wisata Ali Takrim in developing a professional portfolio as an event organizer (EO) to enhance its image and competitiveness in the event management services sector. As the tourism and entertainment industry continues to grow, the need for work documentation and digital portfolios has become crucial for expanding networks and attracting potential clients. The implementation method included initial observation, needs interviews, portfolio design training, and technical assistance in developing effective and communicative portfolio content and layout. The outcome of this activity was the creation of a digital portfolio for Seirah Wisata Ali Takrim, which includes documentation of activities, client testimonials, services, and a business identity that bolsters its credibility as an EO service provider. Keywords: mentoring, portfolio, event organizer, tourism, UMKM.